Market Risk Premium Drives Fair Value in Iraqi Bank Shares - Sami Alasadi, Bushra Mohamed (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
This research investigates the impact of the market risk premium on the fair value of shares in 14 banks listed on the Iraq Stock Exchange, using the CAPM model to estimate the required rate of return. The study addresses the relationship between the risk premium and intrinsic share value, employing statistical analyses including correlation coefficients and regression analyses. Findings reveal a direct, medium-strength relationship between the risk premium and share value, significant at the 0.02 level. The study highlights low return levels and high economic instability in Iraq, leading to decreased fair value of bank shares. Implications suggest the need for strategic investment opportunities and reduced interest rates on short-term loans to stimulate economic growth under unstable conditions.